2016
DOI: 10.1242/dev.127175
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of mouse and human nephron progenitors by the Six family of transcriptional regulators

Abstract: Nephron endowment is determined by the self-renewal and induction of a nephron progenitor pool established at the onset of kidney development. In the mouse, the related transcriptional regulators Six1 and Six2 play non-overlapping roles in nephron progenitors. Transient Six1 activity prefigures, and is essential for, active nephrogenesis. By contrast, Six2 maintains later progenitor selfrenewal from the onset of nephrogenesis. We compared the regulatory actions of Six2 in mouse and human nephron progenitors by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
154
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(167 citation statements)
references
References 81 publications
12
154
0
1
Order By: Relevance
“…Regarding the analysis of the determinants of podocyte differentiation, our study has relevance as podo‐ cyte dedifferentiation may occur in the context of podocyte injuries (17,18). Moreover, previous analyses of the alteration of mitochondrial bioenergetics were performed in diabetic podocytes that were obtained from rats and mice, which could differ from human podocytes (31, 32) or between different mouse strains (33). Moreover, the situation is unclear in mice podocytes, as Wang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the analysis of the determinants of podocyte differentiation, our study has relevance as podo‐ cyte dedifferentiation may occur in the context of podocyte injuries (17,18). Moreover, previous analyses of the alteration of mitochondrial bioenergetics were performed in diabetic podocytes that were obtained from rats and mice, which could differ from human podocytes (31, 32) or between different mouse strains (33). Moreover, the situation is unclear in mice podocytes, as Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…injuries (17,18). Moreover, previous analyses of the alteration of mitochondrial bioenergetics were performed in diabetic podocytes that were obtained from rats and mice, which could differ from human podocytes (31,32) or between different mouse strains (33). Moreover, the situation is unclear in mice podocytes, as Wang et al (34) reported an alteration of oxphos by hyperglycemia, whereas other authors showed the opposite (10,35).…”
Section: Discussionmentioning
confidence: 99%
“…Efforts are already underway in a human GUDMAP initiative (www.gudmap.org). Early studies have revealed some striking differences in Six1 and Six2 regulation within the nephron progenitor compartment (O’Brien et al, 2015). Given the critical role of Six-factors in maintaining nephron progenitors, these results may have relevance to differences in the duration of nephrogenesis and the final nephron count which differ dramatically between mouse and human kidney…”
Section: Man Versus Mousementioning
confidence: 99%
“…Marker lists were exported and compared with published human single cell data 29,30 , and established gene expression profiles from mouse 31 . Gene ontology analysis was performed using TopFunn 32 .…”
Section: Organoid Viability Assessmentmentioning
confidence: 99%